Land Suitability Evaluation for Cocoyam (Colocasia spp) Cultivation on an Acid Soil of Emezhi II in Ahoada - West, Rivers State, Southern Nigeria - K.D. Peter (Journal of the Indian Society of Soil Science, 2023)
for the cultivation of cocoyam. The soil survey and mapping was carried out using the rigid-grid method at semi-detailed level. Three mapping units were identified and subsequently delineated. One modal profile pit (2 m × 2 m) was dug in each of the mapping unit and they were described accordingly. Soil samples were collected from the various horizons for laboratory analysis. The results show that the sand particles were high at surface horizons and decreased down the profile depth. Silt and clay increased down the depth of the profile. The result also revealed that the soils were low in organic carbon, total nitrogen (N), available phosphorus (P) and exchangeable cations. The soil pH was strongly acidic to moderately acidic (4.10-5.0). It was also observed that soils of the study area were not suitable (NS) for cocoyam cultivation due to high flood hazards and low soil depth to water table. Proper timing of planting seasons and adequate drainage management practices can be adopted for cocoyam production on sustainable basis. The ideal soil for cocoyam cultivation is a fertile, well-drained, sandy loam soil with a pH that ranged from acidic to neutral (4.2-7.5). It can also be grown in a variety of conditions including paddies in wetland areas using a system similar to that of rice.